Experience in use of methodology for assessing the qualifications of workers in nuclear industry primary employment - Silenko P. A., Silenko A. N. (Innovative technologies in science and education, 2016)
this work describes of the process of assessment and certification of qualifications of nuclear industry employeess worked out in the context of national qualification system of evaluation on the basis of professional standards development. was conducted The graduates of the Association of supporting high schools of state group of corporations "Rosatom" participated in qualification assessment procedure. The adaptation of computer simulator for nuclear power plant maintenance in operation to be used in the practical part of the certification tests was implemented. The authors have developed an evaluation system of experts social competence on the basis of collaboration with the adapted simulation.
Keywords: компетенция; профессиональный стандарт; competence; оценка квалификаций; Росатом; educational standart; qualification assessment; Rosatom